Yield of Boro rice under system of rice intensification with different water regimes and manural status - Rahman, MJ; Biswas, PK; Amin, AKM R; Zahan, A (Bangladesh Agronomy Journal, 2015)
A field experiment was carried out at the Agronomy Field, Sher-e-Bangla Agricultural University, Dhaka from December, 2011 to May, 2012 to study the yield of Boro rice under system of rice intensification (SRI) with different water regimes and manural status. The experiment consisted of two factors as three water regime viz., waterlogged condition (W1), saturated condition (W2) and alternate wet and dry condition (W3) in the main plots, and six manure and fertilizer combinations viz., cowdung 100% (F1), compost 100% (F2), chemical fertilizer 100% (F3), 50% chemical fertilizer + 25% compost + 25% cowdung (F4), 50% chemical fertilizer + 50% cowdung (F5) and 50% chemical fertilizer + 50% compost (F6) in the sub-plots. Water regime had significant effect on yield and yield components except number of effective tillers m-2, filled grains panicle-1, weight of 1000-grain and harvest index. The highest grain yield (5.74 t ha-1) was obtained from the waterlogged condition that was statistically similar with saturated condition (5.69), whereas alternate wet and dry (AWD) gave the lowest grain yield (4.36 t ha-1). Manural status also significantly influenced yield attributes except 1000-grains weight. The combination of chemical fertilizer, cowdung and compost showed the best performance compared to other manural status. The highest grain yield (5.81 t ha-1) was obtained from chemical fertilizer 50% + cowdung 25% + compost 25% and the lowest grain yield (4.71 t ha-1) was obtained from compost 100%. The highest number of effective tillers hill-1 (33.71) was obtained from compost 100%. Chemical fertilizer 50% + cowdung 25% + compost 25% showed the highest harvest index (46.78%). In case of interaction effect of water regime and manural status the highest grain yield was observed in chemical fertilizer 50% + cowdung 25% + compost 25% of saturated condition (6.80 t ha-1). Bangladesh Agron. J. 2014, 17(2): 1-8